Pengembangan Bahan Ajar Berbasis Literasi Bahasa dan Sains Untuk Sekolah Dasar - Ade Gunawan; Muhamad Alfarisi; Andi Widiono (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The integration of language and science literacy in elementary schools is crucial in 21st-century learning. However, these aspects are often taught separately. Additionally, the lack of integrated teaching materials hinders meaningful learning. This study aims to develop innovative teaching materials based on the integration of language and science literacy for elementary students. The method used is Research and Development (R&D) with the ADDIE model. The development process includes needs analysis, design, development, implementation, and evaluation. Expert validation results show that the materials are categorized as "highly feasible" to "feasible." Limited trials in two elementary classes showed improvements in language and science literacy of 37.1% and 40%, respectively. This study concludes that integrative teaching materials effectively enhance students' literacy and are relevant to support the Merdeka Curriculum.